Association between Overweight, Health Behaviors, and Insulin Resistance in School Children. (19th February 2012) - Hirschler, V.; Molinari, C. G.; Gonzalez, C.
Abstract : The aim of the paper was to determine the association between children's BMI, health behaviors, and HOMA-IR. 1065 students (535M) aged 9.5 ± 2.1  y from 6 schools were examined. Questionnaires for healthy habits were completed. As all components could not contribute equally to overweight/obesity (OW/OB), a multiple regression analysis was done with BMI as the dependent variable. Those components which were associated with BMI were totaled to establish the score. Data also included Tanner, lipids, insulin, and glucose. 165 (15.5%) of the children were OB (BMI > 95%ile per CDC norms), and 152 (14.3%), OW (85 ≤ BMI < 95%ile). Multiple logistic regression analysis showed a positive association between children's OW/OB and HOMA-IR (OR, 2.42 (95% CI 1.97–2.98)), and an inverse association with healthy score (OR, 0.66 (95% CI 0.52–0.85)) adjusted for Tanner and gender. Our results suggest that this is an easy score that could be used to predict children's OW/OB; however additional longitudinal studies should be done to confirm these findings.